Not to Carry Weapons Concealed; Where; nor Sell to Minors, etc., Ch. 43, An Ordinance in Relation to Dangerous and Deadly Weapons, § 1, in The Revised Ordinances of the City of Pattonsburg, Missouri 108 (1902) - (:unkn) unknown (My University, 1902)
Any person, who shall, within the corporate limits of the City of Pattonsburg, carry concealed upon or about his person, any deadly or dangerous weapon, or shall go into any church or place where people have assembled for religious worship, or into any school room or place where people are assembled for educational, literary or social purposes, or to any election precinct, on any election day, or into any court room during the setting of court, or into any other public assemblage of persons met for any lawful purpose, other than for militia drill or meetings called under the militia law of the state of Missouri, having upon or about his person any kind of firearms, bowie knife, dirk, dagger, slung shot or other deadly weapons, or shall, in the presence of one or more persons, exhibit any such weapon in a rude, angry or threatening manner, or shall have or carry any such weapon upon or about his person when intoxicated or under the in§fluence of intoxicating drinks, or shall directly or indirectly, sell or deliver, loan or barter to any minor, any such weapon, without the consent of the parent or guardian of such minor, shall, upon conviction, be fined in any sum not less than twenty-five nor more than one hundred dollars.
Keywords: BRANDISHING; CARRY - CONCEALED; SENSITIVE PLACES; TRANSFER - MINORS